PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 15 PADANG - Fahrezi, Iqbal (Departemen Matematika, 2025)
The results of the end-of-semester assessment, which included number pattern material, showed that the seventh grade class at SMP Negeri 15 Padang continued to show a lack of mathematical understanding. Think Talk Write (TTW), a cooperative learning model, is one model that can be used. The main objective in conducting this study was to compare the model on its effectiveness with direct learning in facilitating learners' mathematical understanding. Grade VIII students from SMP Negeri 15 Padang participated in the study. The research strategy used was quasi-experimental, rooted in the Static Group Design. The participating learners were eighth graders in the 2024-2025 academic year at SMP Negeri 15 Padang. For this sampling, we used a simple random sampling procedure. Based on the draw, the sample group will consist of learners from Class VIII.3 and VIII.6. The research instrument was the deciding factor in the end. A t-test with a significance level of 0.05 yielded a P-value = 0.037, ruling out the null hypothesis (H0), indicating that the P-value < α. This indicates that the TTW model outperformed the direct learning model in improving eighth grade performance at SMP Negeri 15 Padang. According to the findings, this model significantly improved.Keywords – Mathematics learning outcomes, Think Talk Write, Direct learning